A MODIFIED BOUNDARY ELEMENT METHOD FOR SOLVING VIBRATION OF PLATES - V.P. Fedotov (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2011)
This work is devoted to developing algorithms for the solution of wave problems in mathematical physics on the basis of the boundary element method (BEM). The main advantages of the boundary element method is reduced to one dimension of the problem and transfer sample to the boundary of the study area, as well as obtaining a continuous solution in the region. As a consequence, reduces the amount of calculation and improves the accuracy of the solution.